Balligratus, new genus of wingless ground beetles from equatorial Andean montane forest (Coleoptera: Carabidae: Lachnophorini) - Moret, Pierre; Ortuño, Vicente M. (Zootaxa, 2017)
A new carabid beetle genus, Balligratus gen. nov., belonging to the tribe Lachnophorini, is described. It is geographically restricted to the equatorial Andes, and ecologically linked to the montane pluvial forest ecosystem, at elevations ranging from 1,200 to 3,600 m. As other carabid lineages that have radiated in such environments, Balligratus gen. nov. is a wingless clade, characterized by the loss of flight wings associated with metathoracic reduction, constriction of the elytral base, and reduced eye size. This evolution is unique among Lachnophorini. Four new species are described, all of them from Ecuador: Balligratus brevis sp. nov., Balligratus globosus sp. nov., Balligratus gracilis sp. nov. and Balligratus humerangulus sp. nov.